Reconstructing Hydrothermal Fluid Pathways and Storage at the Solfatara Crater (Campi Flegrei, Italy) Using Seismic Scattering and Absorption - Di Martino, Maria Del Pilar; De Siena, Luca; Serlenga, Vincenzo; De Landro, Grazia (Frontiers in Earth Science, 2022)
Campi Flegrei caldera is a high-risk volcano under continuous surveillance due to its closeness to a densely populated area. Volcanic activity inside the caldera is particularly intense at the Solfatara crater, which undergoes strong unrest episodes triggered inside its hydrothermal system. Improving the imaging of the shallow part of this hydrothermal system is crucial to broaden the understanding of unrest processes that are progressively characterizing other portions of the eastern caldera. Seismic attenuation has proven to be a pivotal instrument to map fluid flow at crustal scale. In this study, we mapped seismic absorption from coda wave attenuation and seismic scattering attenuation from peak delay measurements using data from an active seismic survey inside the shallow structure (meter-scale volume) of the Solfatara crater. The frequency-dependent maps provide the first near-surface 3D seismic scattering and absorption model of a hydrothermal system. The scattering contrasts highlight the primary structural feature, a fault separating the hydrothermal plume from zones of CO2 saturation nearing fumaroles. While high-absorption anomalies mark zones of high soil temperatures and CO2 fluxes, low-absorption anomalies indicate zones of very shallow upflow and are caused by contrasts between liquid-rich and vapour-rich fluids coming from mud pools and fumaroles, respectively. All maps show a SW-NE trend in anomalies consistent with fluid-migration pathways towards the eastern fumaroles. The results provide structural constraints that clarify mechanisms of fluid migration inside the crater. The techniques offer complementary geophysical images to the interpretation of hydrothermal processes.